Postoperative Albumin Drop Is a Marker for Surgical Stress and a Predictor for Clinical Outcome: A Pilot Study - Martin Hübner; Styliani Mantziari; Nicolas Demartines; François Pralong; Pauline Coti-Bertrand; Markus Schäfer (Gastroenterology Research and Practice)
Background. Surgical stress during major surgery may be related to adverse clinical outcomes and early quantification of stress response would be useful to allow prompt interventions. The aim of this study was to evaluate the acute phase protein albumin in the context of the postoperative stress response. Methods. This prospective pilot study included 70 patients undergoing frequent abdominal procedures of different magnitude. Albumin (Alb) and C-reactive protein (CRP) levels were measured once daily starting the day before surgery until postoperative day (POD) 5. Maximal Alb decrease (Alb Δ min) was correlated with clinical parameters of surgical stress, postoperative complications, and length of stay. Results. Albumin values dropped immediately after surgery by about 10 g/L (42.2±4.5 g/L preoperatively versus 33.8±5.3 g/L at day 1, P<0.001). Alb Δ min was correlated with operation length (Pearson ρ=0.470, P<0.001), estimated blood loss (ρ=0.605, P<0.001), and maximal CRP values (ρ=0.391, P=0.002). Alb Δ min levels were significantly higher in patients having complications (10.0±5.4 versus 6.1±5.2, P=0.005) and a longer hospital stay (ρ=0.285, P<0.020). Conclusion. Early postoperative albumin drop appeared to reflect the magnitude of surgical trauma and was correlated with adverse clinical outcomes. Its promising role as early marker for stress response deserves further prospective evaluation.